Structural modeling of NAD+ binding modes to PARP-1 - N. V. Ivanisenko; D. A. Zhechev; V. A. Ivanisenko (Вавиловский журнал генетики и селекции, 2017)
The nuclear protein poly (ADP-ribose) polymerase-1 (PARP-1) plays an important role in the signaling and repair of DNA. PARP-1 catalyses covalent binding of poly (ADP-ribose) polymers with itself as well as with other acceptor proteins using NAD+ as a donor of ADP-ribose. Inhibitors of poly (ADP-ribose) polymerase have been shown to be effective in improvement of radiation therapy and chemotherapy of cancer in clinical testing. Development of new poly (ADP-ribose) polymerase-1 inhibitors based on derivatives of natural compounds such as NAD+ represents a novel and promising strategy. The structure of complex of human poly (ADP-ribose) polymerase-1 with NAD+ can be a starting point for rational design of small molecule inhibitors based on NAD+ derivatives. Indeed there is no crystal structure of complex poly (ADP-ribose) polymerase-1 with nicotinamide adenine dinucleotide (NAD+) available yet. In this work using molecular modeling approaches we have predicted NAD+ binding modes with PARP-1 at the donor binding site of the catalytic domain. Using structures of PARP-1 homologs in complex with NAD+ we predicted pharmacophore restraints of NAD+ binding to PARP-1. Based on clustering of PARP-1 conformations in complex with co-crystallized inhibitors and predicted pharmacophore restraints, we proposed several possible models of NAD+ binding to PARP-1 at the donor binding site of the catalytic domain. According to the predicted models, two conformations of pyrophosphate group of NAD+ in complex with PARP-1 at the donor binding site are possible. Validation of the proposed models of NAD+ binding with PARP-1 can be achieved by quantitative structure-activity analysis of NAD+ derivatives. We designed two NAD+ derivatives, which can be used for validation of predicted NAD+ binding models.